2008
DOI: 10.1021/ma801903w
|View full text |Cite
|
Sign up to set email alerts
|

Thiol−Yne Photopolymerizations: Novel Mechanism, Kinetics, and Step-Growth Formation of Highly Cross-Linked Networks

Abstract: Radical-mediated thiol−yne step-growth photopolymerizations are utilized to form highly cross-linked polymer networks. This reaction mechanism is shown to be analogous to the thiol−ene photopolymerization; however, each alkyne functional group is capable of consecutive reaction with two thiol functional groups. The thiol−yne reaction involves the sequential propagation of a thiyl radical with either an alkyne or a vinyl functional group followed by chain transfer of the radical to another thiol. The rate of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
452
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(471 citation statements)
references
References 42 publications
14
452
0
5
Order By: Relevance
“…From the several proposed click type reactions in the literature [326][327], two of them received much attention within the polymer society: Cu(I) catalyzed azide-alkyne cycloaddition (CuAAC) [328][329][330][331][332] and the addition of a thiyl radical to olefins (thiol-ene and thiol-yne) [230,[333][334] (Scheme 2).…”
Section: General Particle Functionalizationmentioning
confidence: 99%
“…From the several proposed click type reactions in the literature [326][327], two of them received much attention within the polymer society: Cu(I) catalyzed azide-alkyne cycloaddition (CuAAC) [328][329][330][331][332] and the addition of a thiyl radical to olefins (thiol-ene and thiol-yne) [230,[333][334] (Scheme 2).…”
Section: General Particle Functionalizationmentioning
confidence: 99%
“…[17][18][19][20][21] It was found earlier that the addition of the first thiol to the alkyne is the rate-limiting step, which is followed by the fast second thiol addition to the intermediate thiol-alkene. 15,16 The conditions and corresponding degree of functionalization by thiol-yne reactions are summarized in Table 4. 1) PU numbers correspond to numbers in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, highly efficient reactive systems that do not contain any metal catalyst are often desired. In this respect, light-mediated thiol-ene 13,14 and thiol-yne [15][16][17][18][19][20][21] radical reactions have become widely used as they effectively combine some classical benefits of coupling reactions with the advantages of a photoinitiated process resulting in a powerful method for chemical synthesis and tailorable material fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…The vinylthioether product is able to undergo a second, faster, regiospecific (2), formally thiol-ene, reaction with the newly generated thiyl radical yielding the intermediate bisthioether radical that undergoes chain transfer with another thiol molecule quantitatively yielding the target bisthioether with exclusive 1,2-orientation. 30 However, one important difference between the radical thiol-ene and radical thiol-yne reactions, at least in the case of the double addition products, is that the thiol-yne reaction of a terminal acetylene results in the generation of a stereocenter and thus the final 1,2-addition product is a mixture of (R) and (S) enantiomers, and as such the radical thiol-yne reaction is not stereoselective.…”
Section: Introductionmentioning
confidence: 99%
“…However, researchers have recently begun to evaluate this potentially highly versatile reaction. Fairbanks et al 30 described radical-mediated thiol-yne stepgrowth polymerization as a route to highly crosslinked networks and conducted a detailed kinetic analysis of the process simultaneously noting the similarities with the radical thiol-ene process. Chan et al 31 reported the synthesis and physical properties of high refractive index polysulfide networks formed via the photopolymerization of a range of alkyldithiols with a series of alkyldiynes, and most recently, Chan, Hoyle, and Lowe 6 described the first example of a sequential, quantitative nucleophilic thiol-ene/radical thiol-yne process for the synthesis of a range of branched structures including examples with potential biomedical significance.…”
Section: Introductionmentioning
confidence: 99%